Infiltrated papules on the trunk and headaches: A case of actinic granuloma and a review of the literature - Sonal A. Parikh, BS; Syril Keena T. Que, MD; William D. Holmes, MD; Katalin Ferenczi, MD; Jane M. Grant-Kels, MD; Marti Jill Rothe, MD (Wolters Kluwer, 2015)
Actinic granuloma is a rare granulomatous reaction that is more commonly seen in females and thought to occur as an autoimmune response to actinic damage of elastic tissue. We discuss a case of a patient with actinic granuloma presenting with concomitant temporal arteritis. Our case and review of the literature emphasize the association between actinic granuloma and temporal arteritis, a serious inflammatory condition that could lead to blindness if misdiagnosed. Keywords: Actinic granuloma, Annular elastolytic giant cell granuloma, Temporal arteritis, Giant cell arteritis